Five year mission : the Labour Party under Ed Miliband - Bale, Tim, 1965- (Oxford University Press, 2015)
In May 2010, Labour suffered one of its worst ever election defeats. A few months later it chose Ed Miliband as its new leader. His task? To win back power after just one term in opposition - a tall order given how many voters had come to blame Labour for the economic mess the country was in, and to see the party as a soft-touch when it came to immigration and welfare. Even those who were more sympathetic had their doubts. Was Ed Miliband really leadership material? Would he be able to overcome defeating his elder brother to get to the top? Would he have to do as he was told by the trade union.